2017
DOI: 10.1001/jamaneurol.2017.2712
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Biomarker Results in Individual Patients With Mild Cognitive Impairment in the Alzheimer’s Biomarkers in Daily Practice (ABIDE) Project

Abstract: IMPORTANCE Biomarkers do not determine conversion to Alzheimer disease (AD) perfectly, and criteria do not specify how to take patient characteristics into account. Consequently, biomarker use may be challenging for clinicians, especially in patients with mild cognitive impairment (MCI). OBJECTIVE To construct biomarker-based prognostic models that enable determination of future AD dementia in patients with MCI. DESIGN, SETTING, AND PARTICIPANTS This study is part of the Alzheimer's Biomarkers in Daily Practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 55 publications
0
91
1
6
Order By: Relevance
“…In a former study, we constructed individualized prognostic models based on MRI and cerebrospinal fluid. This study also showed that biomarkers should best be combined [44].…”
Section: Discussionmentioning
confidence: 59%
“…In a former study, we constructed individualized prognostic models based on MRI and cerebrospinal fluid. This study also showed that biomarkers should best be combined [44].…”
Section: Discussionmentioning
confidence: 59%
“…Characterization of the temporal sequencing of the biomarker cascade shows promise for predicting future cognitive decline, particularly at the patient level, which could dramatically improve late-life planning and outcomes of clinical prevention trials (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cross-sectional analyses of Ab and tau PET imaging have indicated these biomarkers follow hierarchical patterns that may be useful for in vivo disease staging (7,8). Characterization of the temporal sequencing of the biomarker cascade shows promise for predicting future cognitive decline, particularly at the patient level, which could dramatically improve late-life planning and outcomes of clinical prevention trials (9).…”
mentioning
confidence: 99%